Management of Hemodynamic Collapse After Liver Transplantation From Native Bile Duct Stump Hemorrhage with Gelfoam. Issue 10 (October 2019) - Wang, Xiao Jing; Buttar, Navtej; Storm, Andrew C.
Abstract : ABSTRACT: Spontaneous hemobilia is a rare complication after liver transplantation and is largely secondary to the formation of an arteriobiliary fistula, which is generally treated by vascular interventional radiology embolization. We present a case of hemorrhagic shock secondary to arterial hemorrhage at an oversewn bile duct stump after liver transplantation, which failed vascular interventional radiology embolization, and was subsequently controlled using an endoscopic application of a gelatin sponge slurry (Gelfoam). We present this unique approach and review the history of this surgical and interventional hemostasis tool that has not been previously described for endoscopic use.